Outside Back Cover: Volume 2 Issue 3. (30th September 2021) - Geng, Yue; Zhao, Yingjie; Zhao, Jinjin; Zhai, Yu; Yuan, Meng; Wang, Xue‐Dong; Gao, Hanfei; Feng, Jiangang; Wu, Yuchen; Jiang, Lei
Abstract : Outside back cover image : Photo‐responsive materials are a category of smart materials to achieve both spatially and temporally tunable photophysical properties, thus attracting extensive attention for the applications toward multifunctional optoelectronic devices. In this article, the authors realize the optical and electrical modulation within organic one‐dimensional photochromic arrays. Moreover, the ultraviolet photodetectors based on these photochromic arrays exhibit tunable photoresponsivity performance through adjusting their controllable photoisomerization behaviors. The authors believe this work about optoelectronic properties within onecomponent photochromic system will broaden the integration of future multifunctional optoelectronic devices. (DOI: https://doi.org/10.1002/smm2.1056 )